The roles of lifestyle factors and genetic risk in the association between night shift work and cholelithiasis: a prospective cohort study - He, Wangping; Mi, Ningning; Jin, Kecheng; Jin, Boru; Zhong, Ruyang; Liu, Zhen; Lin, Yanyan; Zhang, Hengwei; Yue, Ping; Xia, Bin; He, Qiangsheng; Yuan, Jinqiu; et al. (Frontiers in Endocrinology, 2025)
BackgroundNight shift work has been associated with adverse health outcomes. Whether night shift work is associated with cholelithiasis remains uncertain, and the roles of genetic risk and lifestyle factors in cholelithiasis risk are unclear.MethodsWe conducted a prospective analysis of 219,810 UK Biobank participants. Cox proportional hazards models were used to estimate the association between night shift work and incident cholelithiasis. Polygenic risk score analyses and causal mediation analyses were performed to investigate the roles of the genetic risk and lifestyle factors in cholelithiasis risk.ResultsCompared with day workers, the HR and 95% CI of cholelithiasis was 1.09 (1.01-1.17) for individuals with rarely/some night shifts and 1.18 (1.04-1.35) for those with usual/permanent night shifts. Additionally, those with a higher frequency of night shifts and a longer length of each night shift were associated with an increased risk of cholelithiasis. Notably, individuals with usual/permanent night shifts and high genetic risk exhibited the highest risk of cholelithiasis (HR: 1.48, 95% CI: 1.21-1.81). Mediation analysis indicated that a substantial portion (24.64%) of the association was mediated by BMI, followed by unhealthy alcohol intake (4.50%) and sedentary time (1.82%).ConclusionsNight shift work is associated with an increased risk of cholelithiasis, with this relationship being largely mediated by lifestyle factors. Reducing the frequency and length of night shifts may help mitigate the incidence of cholelithiasis among night shift workers, particularly for those with heightened genetic susceptibility.